Preliminary study on frequency characteristics of air coil for oil palm fruit sensor - N. H., Harun; M., Norhisam; Hiroyuki, Wakiwaka; I., Aris; R. M., Sidek (2012)
The development of oil palm fruit sensor based on eddy current method is introduced in this paper. Initially, the frequency characteristics of the air coil of the sensor are investigated to determine the value of resonant frequency along with the inductance and resistance characteristics of the air coil. The diameter of the air coil is fixed at a value of 24mm throughout the investigations. Ten samples from two categories namely the ripe oil palm fruitlet and unripe oil palm fruit let are used in this study. All samples are tested up from 100 Hz to 1 MHz frequency, The resonant frequency of the air coil is obtained at 6.3MHz, The pertaining results showed that the inductance and the resistance characteristics of the air coil sensor provide significant changes among the samples of each category. Finally the paper evaluates the frequency characteristics of the air coil in designing the oil palm sensor based on the eddy current method. The designed sensor exhibits significant potential in ·determining the maturity of oil palm fruit.